(untitled) (Journal of Surgical Sciences, 2019)
The objective of the study was to find out the prevalence of gallbladder carcinoma in patients having cholelithiasis. For this purpose a prospective study was carried out on 15 patients of both sexes in Shaheed Ziaur Rahman Medical College Hospital, Bogura. Their mean age was 56 ±8 years (range 30 to 70 years) having gall bladder mass. Gall bladder mass and stone were detected by history, Physical examination, ultrasonography and computed tomography of the abdomen. Carcinoma was confirmed by histopathological examination of specimens removed by operation. All gallbladder masses removed by operation showed malignat tumor on histopathological examination. Among them adenocarcinoma and squamous cell carcinoma were present in 94 and 6 percent respectively. Stones were present within gallbladder mass in 94 percent of cases. In 80 percent of cases the disease was in advanced stage. The results of the present study suggested that the patient having cholelithiasis are prone to develop malignancy in the gallbladder. However as the sample size is small further studies are needed by taking large number of sample to validate this statement Journal of Surgical Sciences (2012) Vol. 16 (2) : 68-70